HTTP protocols - Grigorik, Ilya (O'Reilly, 2017)
Prepare yourself for building fast and efficient web applications. Take a brief historical tour of the evolution of the HTTP protocol. Understanding of the key design changes of HTTP, and the motivations behind each, will give us the necessary background for our discussions on HTTP performance, especially in the context of the many upcoming improvements in HTTP 2.0.